Peran Kurikulum Pesantren dalam Membentuk Karakter Santri Pondok Pesantren Mambaul Ulum Bata-Bata Putri Panaan Palengaan Pamekasan - Ummi Fauzah Asysyafiqoh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
This research was conducted because of the urgency of the pesantren curriculum as the basis and pace of education in pesantren. The curriculum should be more devoted to its role in the formation of the character of students who cannot be separated from the system and curriculum design being implemented. The formulation of the problem of this thesis are: First, How is the Curriculum System at Mambaul Ulum Bata Bata-Bata Islamic Boarding School, Second, How is the character of the students of Mambaul Ulum Bata Bata Islamic Boarding School, Third, How is the Role of Islamic Boarding School Curriculum in Shaping the Character of Pamekasan Mambaul Ulum Islamic Boarding School Students. This research is a field research that collects primary data through interviews from the leadership and families of the pesantren leadership, the Ma'hadiyah Council, the teacher council, management staff and students, while the secondary data is obtained from literature and documents of the Mambaul Ulum Islamic Boarding School Bata-Bata. In the end, the data collected were followed by qualitative analysis and described in descriptive form. The results of the study concluded that the curriculum at Mambaul Ulum Bata-Bata Islamic Boarding School includes a semi-Salaf curriculum. In addition to pesantren having special guidelines in the pace of education, the national curriculum is also implemented in formal education. Moreover, it is integrated so that it provides a special style and its own role in the formation of the character of students based on the motto and philosophy upheld by the Mambaul Ulum Islamic Boarding School Bata-Bata which is Panaan Palengaan Pamekasan.Â Penelitian ini dilakukan kerena dilatar belakangi urgensi kurikulum pesantren sebagai pijakan dasar dan laju penyelenggaraan pendidikan di pesantren yang dalam hal ini lebih dikhususkan pada peranannya dalam pembentukan karakter santri yang tidak lepas dari sistem dan pola kurikulum pesantren yang diimplementasikan. Rumusan masalah dari tesis ini adalah Pertama, Bagaimana Sistem KurikulumÂ di Pondok Pesantren Mambaul Ulum Bata-Bata Pamekasan, Kedua, Bagaimana karakter santri Pondok Pesantren Mambaul Ulum Bata-Bata, Ketiga, Bagaimana Peran Kurikulum Pesantren dalam Membentuk Karakter Santri Mambaul Ulum Bata-Bata Pamekasan. Jenis penelitia ini adalah penelitian lapangan yang menghimpun data primer melaului wawancara dari pihak pimpinan dan keluarga pimpinan pesantren, Dewan Maâ€™hadiyah, Dewan guru, Staf pengelola dan santri, adapun data Skunder didapat dari lieteratur dan dokumen Pondok Pesantren Mambaul Ulum Bata-Bata, setelah semua data terkumpul dilanjut analisis kulitatif dan diuraikan dalam bentuk diskriptif. Hasil dari penelitian menyimpulkan bahwa kurikulum di Pondok Pesantren Mambaul Ulum Bata-Bata mencakup kurikulum semi salaf, selain pesantren memiliki pedoman khusus dalam laju pendidikan, juga kurikulum nasional diimplementasikan dalam pendidikan formal yang kemudian terintegrasi sehingga memberikan corak khusus serta peran tersendiri terhadap pembentukan karakter santri berdasarkan motto dan falsafah yang dijunjung tinggi oleh Pondok Pesantren Mambaul Ulum Bata-Bata Panaan Palengaan Pamekasan.